Konsumerisme: "Penjara" Baru Hakikat Manusia? - Andreas Maurenis Putra (Societas Dei: Jurnal Agama dan Masyarakat, 2018)
ABSTRACT: Consuming goods for the necessities of life is a natural thing. However, consuming that exceeds the limit until wasting should be avoided. The dilemma of human needs today presents a new phenomenon in terms of fulfilling the necessities of life. This phenomenon is none other than-widely known by society- consumerism. The process is to use goods of production in excess or inappropriate manner consciously and sustainably. So, this phenomenon (consumerism) continues to be one of the central themes in this era of globalization. Unfortunately, the ferocity of this ideological influence ostracizes the fundamental values that exist within each individual. Consumerism eliminates the significance of the basic essence that exists in man. Humans who should remember the nature of themselves as social beings who are always connected to one another in this cosmos are now slowly losing that meaning. With the mindset and lifestyle of consumptive, human as if imprisoned and alienated. Quality of life is no longer measured based on the value of meaningfulness for others and the environment but measured by materials. This consequence becomes a fundamental crisis which is humans essence degradation. KEYWORDS: Consumerism, Identity, Behaviour, Imprisoned, Awarness, Social Person,Religious Person, Threatment, Simplicity